Costs of streamlined HIV care delivery in rural Ugandan and Kenyan clinics in the SEARCH Study. (24th September 2018) - Shade, Starley B.; Osmand, Thomas; Luo, Alex; Aine, Ronald; Assurah, Elly; Mwebaza, Betty; Mwai, Daniel; Owaraganise, Asiphas; Mwangwa, Florence; Ayieko, James; Black, Douglas; Brown, Lillian B.; et al.
Abstract : Objectives/design: As antiretroviral therapy (ART) rapidly expands in sub-Saharan Africa using new efficient care models, data on costs of these approaches are lacking. We examined costs of a streamlined HIV care delivery model within a large HIV test-and-treat study in Uganda and Kenya. Methods: We calculated observed per-person-per-year (ppy) costs of streamlined care in 17 health facilities in SEARCH Study intervention communities (NCT: 01864603) via micro-costing techniques, time-and-motion studies, staff interviews, and administrative records. Cost categories included salaries, ART, viral load testing, recurring goods/services, and fixed capital/facility costs. We then modeled costs under three increasingly efficient scale-up scenarios: lowest-cost ART, centralized viral load testing, and governmental healthcare worker salaries. We assessed the relationship between community-specific ART delivery costs, retention in care, and viral suppression. Results: Estimated streamlined HIV care delivery costs were 291/ppy. ART (117/ppy for TDF/3TC/EFV [40%]) and viral load testing (110/ppy for 2 tests/year [39%]) dominated costs versus salaries (51/ppy), recurring costs (5/ppy), and fixed costs (7/ppy). Optimized ART scale-up with lowest-cost ART (100/ppy), annual viral load testing (24/ppy), and governmental healthcare salaries (27/ppy), lowered streamlined care cost to 163/ppy. We found clinic-to-clinic heterogeneity in retention and viral suppression levels versus streamlined care delivery costs, but no correlation between cost and either retention or viral suppression. Conclusions: In the SEARCH Study, streamlined HIV care delivery costs were similar to or lower than prior estimates despite including viral load testing; further optimizations could substantially reduce costs further. These data can inform global strategies for financing ART expansion to achieve UNAIDS 90–90–90 targets. Abstract : Supplemental Digital Content is available in the text